Ichthyoses: new insights unravel defects in skin barrier function resulting in diverse clinical and morphological phenotypes - Haußer-Siller, Ingrid (British journal of dermatology, 2017)
Linked Article: Gruber et al. Br J Dermatol 2017; 176:1068-1073.